An Interfacial Solar‐Driven Atmospheric Water Generator Based on a Liquid Sorbent with Simultaneous Adsorption–Desorption. Issue 43 (15th September 2019) - Qi, Heshan; Wei, Tianqi; Zhao, Wei; Zhu, Bin; Liu, Guoliang; Wang, Pingping; Lin, Zhenhui; Wang, Xueyang; Li, Xiuqiang; Zhang, Xiaowei; Zhu, Jia
Abstract: Water scarcity is one of the greatest challenges facing human society. Because of the abundant amount of water present in the atmosphere, there are significant efforts to harvest water from air. Particularly, solar‐driven atmospheric water generators based on sequential adsorption–desorption processes are attracting much attention. However, incomplete daytime desorption is the limiting factor for final water production, as the rate of water desorption typically decreases very quickly with decreased water content in the sorbents. Hereby combining tailored interfacial solar absorbers with an ionic‐liquid‐based sorbent, an atmospheric water generator with a simultaneous adsorption–desorption process is generated. With enhanced desorption capability and stabilized water content in the sorbent, this interfacial solar‐driven atmospheric water generator enables a high rate of water production (≈0.5 L m −2 h −1 ) and 2.8 L m −2 d −1 for the outdoor environment. It is expected that this interfacial solar‐driven atmospheric water generator, based on the liquid sorbent with a simultaneous adsorption–desorption process opens up a promising pathway to effectively harvest water from air. Abstract : A novel interfacial solar‐driven atmospheric water generator can simultaneously adsorb and desorb water based on a liquid sorbent, 1‐ethyl‐3‐methyl‐imidazolium acetate. With enhanced desorption capability and continuous water supplement in the sorbent, this atmospheric water generator can achieve a high rate of water production (≈0.5 L m −2 h −1 ) and 2.8 L m −2 d −1 for the outdoor environment.